Preparation method of special titanium dioxide for road sign paint
Through the combination technology of modified dispersant and envelope material, the problem of insufficient yellowing resistance and high temperature resistance of titanium dioxide for road sign paint in high temperature and ultraviolet environments is solved, which significantly improves its dispersion and glossiness and improves the road The stability and visual effects of the logo.
Patent Information
- Application Number
- CN202411213033.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-10
AI Technical Summary
The existing titanium dioxide for road sign paint shows poor yellowing resistance, high temperature and gloss resistance in extreme environments such as high temperature and ultraviolet rays, affecting the stability and visual effect of road signs.
Using the combination technology of modified dispersant and envelope material, modifying dispersant is prepared by raw materials such as allyl alcohol polyoxyethylene ether, acrylic acid and 3-(isobutenyloxy)propyltris(trimethylsiloxane)silane. The film and film envelope are used for surface treatment and film encapsulation of titanium dioxide, respectively, to form a stable adsorption layer and esterification reaction, to enhance its dispersion, high temperature resistance and glossiness.
It significantly improves the dispersion, yellowing resistance and high temperature resistance of titanium dioxide, forming a smoother and uniform coating film, enhancing the color brightness and durability of road sign paint, and improving the clarity and safety of road signs.
Smart Images

Figure BDA0005020756250000031 
Figure BDA0005020756250000041
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium dioxide preparation, and in particular relates to a method for preparing titanium dioxide special for road marking paint. Background Art
[0002] As road traffic becomes increasingly busy, road sign paint, as an important sign to ensure driving safety, has increasingly stringent performance requirements. Titanium dioxide is the core pigment of road sign paint, and its yellowing resistance is directly related to the color stability of road sign paint during long-term use. Due to environmental factors such as ultraviolet rays, high temperature, and humidity, traditional titanium dioxide is prone to yellowing, causing the color of road sign paint to fade, affecting driving safety. At the same time, as road construction extends to extreme environments such as high temperature and high humidity, the high temperature resistance of road sign paint is also particularly important. High temperature resistant titanium dioxide can maintain stable physical and chemical properties under high temperature conditions, prevent road sign paint from softening, deforming or falling off due to high temperature, and ensure the clarity and durability of road signs. In addition, high gloss titanium dioxide can enhance the visual effect of road sign paint, make road signs more eye-catching, and improve driving safety. Therefore, by continuously optimizing the preparation process and surface treatment technology of titanium dioxide, its application performance in road sign paint can be improved to meet the increasingly high road safety standards and environmental protection requirements.
[0003] Patent CN 112759948 B discloses a titanium dioxide powder for road sign paint and a preparation method thereof, the method comprising: mixing metatitanic acid, KOH, Al2(SO4)3 and phosphoric acid, squeezing the obtained salt-treated metatitanic acid to a moisture content of less than 50%, and calcining; crushing the obtained calcined product, dispersing, and performing hydrocyclone separation to obtain titanium dioxide slurry; heating the titanium dioxide slurry, adding sodium hexametaphosphate solution, adjusting the pH value to 6.5-7.5, then adding Zr(SO4)2 solution, adjusting the pH value to 8.3-8.7, and then After adding sodium hexametaphosphate solution for the first time, the pH value is adjusted to 10.2-10.7, and NaAlO2 solution is added while maintaining the above pH value to adjust the pH value to 5.8-6.2, and the mixture is aged to obtain a coated slurry; the coated slurry is washed with water, dried, crushed, and then mixed with an organic treatment agent to obtain titanium dioxide for road sign paint. The titanium dioxide for road sign paint obtained by this method has excellent yellowing resistance and weather resistance, but its high temperature resistance, glossiness, dispersibility and yellowing resistance still have room for improvement. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing titanium dioxide for road sign paint, so as to solve the technical problems of poor high temperature resistance, glossiness, dispersibility and yellowing resistance of titanium dioxide for road sign paint in the prior art.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The present invention provides a method for preparing titanium dioxide powder for road marking paint, comprising the following steps:
[0007] Step (1): adding the primary titanium dioxide product to a sodium hydroxide solution, heating and stirring the solution, and after the treatment, washing and drying the solution to obtain modified titanium dioxide;
[0008] Step (2): mixing the modified titanium dioxide with deionized water, crushing and wet-grinding the mixture, and then mixing the wet-grinded modified titanium dioxide with a modified dispersant, and sand-grinding the mixture to obtain a sand-grinded slurry;
[0009] Step (3): Add the sand-ground slurry to a coating device with a stirring device, add deionized water for dilution, start the stirring device, then add the coating material, mature, dry, and crush to obtain titanium dioxide for road sign paint.
[0010] Preferably, in step (1), the ratio of the primary titanium dioxide to the sodium hydroxide solution is (3-8) g: (20-30) mL, the mass fraction of the sodium hydroxide solution is 40 wt %, the heating temperature is 60-70° C., and the stirring time is 6-8 h.
[0011] Preferably, in the step (2), the amount ratio of modified titanium dioxide, deionized water and modified dispersant is (20-40) g: (30-50) mL: (2-5) g, and a vertical sand mill is used during the sand grinding process. The particle size of the sanded slurry after sand grinding is 0.2-0.3 μm, and the particle size distribution is 1.30-1.38.
[0012] Preferably, in step (2), the method for preparing the modified dispersant comprises the following steps:
[0013] Q1: Allyl alcohol polyoxyethylene ether and thioglycolic acid are mixed and added to a four-necked flask, and deionized water is added to dissolve them. At the same time, ammonium persulfate is dissolved in deionized water to obtain an ammonium persulfate solution, acrylic acid is dissolved in deionized water to obtain an acrylic acid solution, 3-(isobutyleneoxy)propyltri(trimethylsiloxane)silane is dissolved in methanol to obtain a silane solution, the ammonium persulfate solution, the acrylic acid solution and the silane solution are connected to the four-necked flask through a constant flow pump, and the four-necked flask is heated;
[0014] Q2: When the temperature of the four-necked flask rises to the reaction temperature, start to drop the ammonium persulfate solution, then start to drop the acrylic acid solution, and finally drop the silane solution, control the dropping time, and after the dropping is completed, carry out the heat preservation reaction;
[0015] Q3: After the heat preservation reaction is completed, the temperature is lowered, the pH is adjusted, and the modified dispersant is obtained by rotary evaporation.
[0016] In the above process, the synthetic reaction formula of the modified dispersant is as follows:
[0017]
[0018] Preferably, in Q1, the molar ratio of allyl alcohol polyoxyethylene ether, acrylic acid and 3-(isobutyleneoxy)propyl tris(trimethylsiloxane)silane is (3-6):(1-2):(0.5-3); in Q2, the reaction temperature is 50-60°C, the acrylic acid solution is added dropwise after 3-5 minutes, and the silane solution is added dropwise after 6-10 minutes, and the dropping time is controlled to be 50-60 minutes, and the acrylic acid solution is added first, followed by the silane solution, and the ammonium persulfate solution is added last, and the insulation reaction time is 3-5 hours; in Q3, the temperature is lowered to 28-30°C, the pH is adjusted to 7-7.2 with 30vt% sodium hydroxide, and the rotary evaporation temperature is 60-70°C.
[0019] Preferably, in step (3), the ratio of the amount of sand-grinding slurry, deionized water and coating material is (20-30) g: (60-80) mL: (18-27) g, and the aging time is 30-120 min.
[0020] Preferably, the method for preparing the coating material comprises the following steps:
[0021] S1: After mixing methyl methacrylate and butyl acrylate, potassium persulfate is added, and the mixture is heated and stirred for reaction. After the reaction is completed, 2-ethylhexyl acrylate is added and reacted to obtain an intermediate product;
[0022] S2: Add acrylic acid to the intermediate product and heat to react. After the reaction is completed, a coating material is obtained.
[0023] In the above process, the synthetic reaction formula of the coating material is as follows:
[0024]
[0025] Preferably, in S1, the molar ratio of methyl methacrylate, butyl acrylate and 2-ethylhexyl acrylate is (0.9-1.2):(1-1.2):(0.9-1.1), the heating temperature is 70-74°C, the reaction time is 0.5-1h, and the reaction temperature after adding 2-ethylhexyl acrylate is 70-74°C, and the reaction time is 5-5.5h.
[0026] Preferably, in S2, the molar ratio of the intermediate product to acrylic acid is (0.9-1.2):(0.8-1.2), the heating temperature is 80-82°C, and the reaction time is 0.5-1h.
[0027] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0028] 1. The present invention firstly uses allyl alcohol polyoxyethylene ether, acrylic acid and 3-(isobutylene acyloxy)propyl tris(trimethylsiloxane) silane as raw materials to prepare a modified dispersant, and then uses methyl methacrylate, butyl acrylate and acrylic acid as raw materials to prepare a coating material. The modified dispersant and the coating material are simultaneously applied to the preparation of titanium dioxide for road marking paint, so that the titanium dioxide has excellent dispersibility, yellowing resistance, high temperature resistance and high gloss.
[0029] 2. The present invention uses allyl alcohol polyoxyethylene ether, acrylic acid and 3-(isobutylene acyloxy)propyl tri(trimethylsiloxane) silane as raw materials, thioglycolic acid as a chain transfer agent, and ammonium persulfate as an initiator to prepare a modified dispersant, which is used in titanium dioxide for road sign paint to effectively improve its dispersibility, yellowing resistance and high temperature resistance. The modified dispersant can form a stable adsorption layer on the surface of the modified titanium dioxide, effectively prevent agglomeration between particles, and improve the dispersion uniformity of titanium dioxide in the road sign paint, so that the coating formed by the road sign paint is smoother and more uniform; The siloxane groups contained in the 3-(isobutyleneoxy)propyltri(trimethylsiloxane)silane in the raw materials are hydrolyzed to generate silanol groups, which undergo condensation reactions with the hydroxyl groups on the surface of the modified titanium dioxide to form strong chemical bonds, thereby improving the binding force between the dispersant and the titanium dioxide particles while also improving its high temperature resistance. The presence of siloxane can also increase its oxidation resistance and protect the titanium dioxide particles from yellowing in harsh environments such as high temperature and ultraviolet rays, thereby improving the color brightness and durability of road sign paints and improving the clarity and safety of road signs.
[0030] 3. The present invention uses methyl methacrylate, butyl acrylate and acrylic acid as raw materials to prepare a coating material. The carboxyl group contained in the coating material can undergo an esterification reaction with the hydroxyl group on the surface of titanium dioxide to generate ester bonds and water, which can enhance the binding force between the coating material and titanium dioxide. The esterification reaction allows the coating material molecules to be tightly combined with the surface of titanium dioxide particles, reducing the gaps and defects between the interfaces, increasing the flatness and smoothness of the surface, reducing the scattering and diffuse reflection of light, allowing more light to be emitted from the surface of the coating layer in the form of mirror reflection, thereby increasing the glossiness of titanium dioxide. At the same time, the presence of the coating layer can reduce the defects and roughness of the surface of the titanium dioxide particles, reducing the obstacles encountered by light during propagation, and further increasing the glossiness. DETAILED DESCRIPTION
[0031] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] This embodiment discloses a method for preparing a modified dispersant, comprising the following steps:
[0034] Q1: 6.65 g of allyl alcohol polyoxyethylene ether and 0.033 mL of thioglycolic acid were mixed and added to a four-necked flask, and 50 mL of deionized water was added for dissolution. At the same time, 0.007 g of ammonium persulfate was dissolved in 10 mL of deionized water to obtain an ammonium persulfate solution, 1.5 mL of acrylic acid was dissolved in 20 mL of deionized water to obtain an acrylic acid solution, 11.76 mL of 3-(isobutylene acyloxy)propyl tris(trimethylsiloxane)silane was dissolved in 20 mL of methanol to obtain a silane solution, and the ammonium persulfate solution, the acrylic acid solution and the silane solution were connected to the four-necked flask by a constant flow pump, and the four-necked flask was heated;
[0035] Q2: When the temperature of the four-necked flask rises to 55°C, start to drop the ammonium persulfate solution, start to drop the acrylic acid solution 3 minutes later, and add the silane solution 8 minutes later. The dropping time is controlled to be 55 minutes. After the dropping is completed, keep the temperature for reaction for 5 hours;
[0036] Q3: After the heat preservation reaction is completed, the temperature is lowered to 28°C, the pH is adjusted to 7 with 30vt% sodium hydroxide, and the modified dispersant is obtained by rotary evaporation at 65°C.
[0037] This embodiment discloses a method for preparing a coating material, comprising the following steps:
[0038] S1: After mixing 1.23 mL of methyl methacrylate and 1.85 mL of butyl acrylate, 0.003 g of potassium persulfate was added, and the mixture was heated and stirred at 74°C for 0.5 h. After the reaction was completed, 2.07 g of 2-ethylhexyl acrylate was added, and the mixture was reacted at 74°C for 5 h to obtain an intermediate product;
[0039] S2: Add 1.25 mL of acrylic acid to 7.90 g of the intermediate product, heat to 82° C. for reaction for 0.5 h, and after the reaction is completed, obtain a coating material.
[0040] This embodiment discloses a method for preparing titanium dioxide for road marking paint, comprising the following steps:
[0041] Step (1): adding 5.5 g of the primary titanium dioxide to 25 mL of a 40 wt% sodium hydroxide solution, heating and stirring at 65° C. for 8 h, washing and drying after the treatment to obtain modified titanium dioxide;
[0042] Step (2): 30 g of modified titanium dioxide was mixed with 40 mL of deionized water, and then crushed and wet-milled. Then, the wet-milled modified titanium dioxide was mixed with 3.5 g of a modified dispersant, and sand-milled using a vertical sand mill. The particle size of the sand-milled slurry after sand milling was 0.25 μm, and the particle size distribution was 1.33, to obtain a sand-milled slurry;
[0043] Step (3): Add 25 g of the sand-ground slurry to a coating device with a stirring device, add 70 mL of deionized water for dilution, start the stirring device, then add 22.5 g of the coating material, mature for 120 min, dry, and crush to obtain titanium dioxide for road sign paint.
[0044] Example 2
[0045] This embodiment discloses a method for preparing a modified dispersant, comprising the following steps:
[0046] Q1: 4.47 g of allyl alcohol polyoxyethylene ether and 0.033 mL of thioglycolic acid were mixed and added to a four-necked flask, and 50 mL of deionized water was added for dissolution. At the same time, 0.007 g of ammonium persulfate was dissolved in 10 mL of deionized water to obtain an ammonium persulfate solution, 1 mL of acrylic acid was dissolved in 20 mL of deionized water to obtain an acrylic acid solution, 3.36 mL of 3-(isobutylene acyloxy)propyl tris(trimethylsiloxane)silane was dissolved in 20 mL of methanol to obtain a silane solution, and the ammonium persulfate solution, acrylic acid solution and silane solution were connected to the four-necked flask by a constant flow pump, and the four-necked flask was heated;
[0047] Q2: When the temperature of the four-necked flask rises to 55°C, start to drop the ammonium persulfate solution, start to drop the acrylic acid solution 3 minutes later, and add the silane solution 8 minutes later. The dropping time is controlled to be 55 minutes. After the dropping is completed, keep the temperature for reaction for 5 hours;
[0048] Q3: After the heat preservation reaction is completed, the temperature is lowered to 28°C, the pH is adjusted to 7 with 30vt% sodium hydroxide, and the modified dispersant is obtained by rotary evaporation at 65°C.
[0049] This embodiment discloses a method for preparing a coating material, comprising the following steps:
[0050] S1: After mixing 1.06 mL of methyl methacrylate and 1.59 mL of butyl acrylate, 0.003 g of potassium persulfate was added, and the mixture was heated and stirred at 74°C for 0.5 h. After the reaction was completed, 1.84 g of 2-ethylhexyl acrylate was added, and the mixture was reacted at 74°C for 5 h to obtain an intermediate product;
[0051] S2: Add 1 mL of acrylic acid to 6.77 g of the intermediate product, heat to 82° C. for 0.5 h, and after the reaction is completed, a coating material is obtained.
[0052] This embodiment discloses a method for preparing titanium dioxide for road marking paint, comprising the following steps:
[0053] Step (1): adding 3 g of the primary titanium dioxide product to 20 mL of a sodium hydroxide solution having a mass fraction of 40 wt%, heating and stirring at 65° C. for 8 h, washing and drying after the treatment to obtain modified titanium dioxide;
[0054] Step (2): 20 g of modified titanium dioxide was mixed with 30 mL of deionized water, and then crushed and wet-milled. Then, the wet-milled modified titanium dioxide was mixed with 2 g of a modified dispersant, and sand-milled using a vertical sand mill. The sand-milled slurry had a particle size of 0.25 μm and a particle size distribution of 1.33, thereby obtaining a sand-milled slurry.
[0055] Step (3): Add 20 g of the sand-ground slurry to a coating device with a stirring device, add 60 mL of deionized water for dilution, start the stirring device, then add 18 g of the coating material, mature for 120 min, dry, and crush to obtain titanium dioxide for road sign paint.
[0056] Example 3
[0057] This embodiment discloses a method for preparing a modified dispersant, comprising the following steps:
[0058] Q1: 8.94 g of allyl alcohol polyoxyethylene ether and 0.033 mL of thioglycolic acid were mixed and added to a four-necked flask, and 50 mL of deionized water was added for dissolution. At the same time, 0.007 g of ammonium persulfate was dissolved in 10 mL of deionized water to obtain an ammonium persulfate solution, 2 mL of acrylic acid was dissolved in 20 mL of deionized water to obtain an acrylic acid solution, 20.16 mL of 3-(isobutylene acyloxy)propyl tris(trimethylsiloxane) silane was dissolved in 20 mL of methanol to obtain a silane solution, and the ammonium persulfate solution, acrylic acid solution and silane solution were connected to the four-necked flask by a constant flow pump, and the four-necked flask was heated;
[0059] Q2: When the temperature of the four-necked flask rises to 55°C, start to drop the ammonium persulfate solution, start to drop the acrylic acid solution 3 minutes later, and add the silane solution 8 minutes later. The dropping time is controlled to be 55 minutes. After the dropping is completed, keep the temperature for reaction for 5 hours;
[0060] Q3: After the heat preservation reaction is completed, the temperature is lowered to 28°C, the pH is adjusted to 7 with 30vt% sodium hydroxide, and the modified dispersant is obtained by rotary evaporation at 65°C.
[0061] This embodiment discloses a method for preparing a coating material, comprising the following steps:
[0062] S1: After mixing 1.41 mL of methyl methacrylate and 1.91 mL of butyl acrylate, 0.003 g of potassium persulfate was added, and the mixture was heated and stirred at 74°C for 0.5 h. After the reaction was completed, 2.25 g of 2-ethylhexyl acrylate was added, and the mixture was reacted at 74°C for 5 h to obtain an intermediate product;
[0063] S2: Add 1.5 mL of acrylic acid to 9.02 g of the intermediate product, heat to 82° C. for 0.5 h, and after the reaction is completed, a coating material is obtained.
[0064] This embodiment discloses a method for preparing titanium dioxide for road marking paint, comprising the following steps:
[0065] Step (1): adding 8 g of the primary titanium dioxide to 30 mL of a 40 wt% sodium hydroxide solution, heating and stirring at 65° C. for 8 h, washing and drying after the treatment to obtain modified titanium dioxide;
[0066] Step (2): 40 g of modified titanium dioxide was mixed with 50 mL of deionized water, and then crushed and wet-milled. Then, the wet-milled modified titanium dioxide was mixed with 5 g of a modified dispersant, and sand-milled using a vertical sand mill. The particle size of the sand-milled slurry after sand milling was 0.25 μm, and the particle size distribution was 1.33, to obtain a sand-milled slurry;
[0067] Step (3): Add 30 g of the sand-ground slurry to a coating device with a stirring device, add 80 mL of deionized water for dilution, start the stirring device, then add 27 g of the coating material, mature for 120 min, dry, and crush to obtain titanium dioxide for road sign paint.
[0068] Example 4
[0069] This embodiment discloses a method for preparing a modified dispersant, comprising the following steps:
[0070] Q1: 5.72 g of allyl alcohol polyoxyethylene ether and 0.033 mL of thioglycolic acid were mixed and added to a four-necked flask, and 50 mL of deionized water was added for dissolution. At the same time, 0.007 g of ammonium persulfate was dissolved in 10 mL of deionized water to obtain an ammonium persulfate solution, 1.7 mL of acrylic acid was dissolved in 20 mL of deionized water to obtain an acrylic acid solution, 7.53 mL of 3-(isobutylene acyloxy)propyl tris(trimethylsiloxane)silane was dissolved in 20 mL of methanol to obtain a silane solution, and the ammonium persulfate solution, acrylic acid solution and silane solution were connected to the four-necked flask by a constant flow pump, and the four-necked flask was heated;
[0071] Q2: When the temperature of the four-necked flask rises to 55°C, start to drop the ammonium persulfate solution, start to drop the acrylic acid solution 3 minutes later, and add the silane solution 8 minutes later. The dropping time is controlled to be 55 minutes. After the dropping is completed, keep the temperature for reaction for 5 hours;
[0072] Q3: After the heat preservation reaction is completed, the temperature is lowered to 28°C, the pH is adjusted to 7 with 30vt% sodium hydroxide, and the modified dispersant is obtained by rotary evaporation at 65°C.
[0073] This embodiment discloses a method for preparing a coating material, comprising the following steps:
[0074] S1: After mixing 1.13 mL of methyl methacrylate and 1.71 mL of butyl acrylate, 0.003 g of potassium persulfate was added, and the mixture was heated and stirred at 74°C for 0.5 h. After the reaction was completed, 1.93 g of 2-ethylhexyl acrylate was added, and the mixture was reacted at 74°C for 5 h to obtain an intermediate product;
[0075] S2: Add 1.17 mL of acrylic acid to 7.13 g of the intermediate product, heat to 82° C. for 0.5 h, and after the reaction is completed, a coating material is obtained.
[0076] This embodiment discloses a method for preparing titanium dioxide for road marking paint, comprising the following steps:
[0077] Step (1): adding 7 g of the primary titanium dioxide product to 22 mL of a 40 wt% sodium hydroxide solution, heating and stirring at 65° C. for 8 h, washing and drying after the treatment to obtain modified titanium dioxide;
[0078] Step (2): 25 g of modified titanium dioxide was mixed with 35 mL of deionized water, and then crushed and wet-milled. Then, the wet-milled modified titanium dioxide was mixed with 3 g of a modified dispersant, and sand-milled using a vertical sand mill. The sand-milled slurry had a particle size of 0.25 μm and a particle size distribution of 1.33, thereby obtaining a sand-milled slurry.
[0079] Step (3): Add 22 g of the sand-ground slurry to a coating device with a stirring device, add 65 mL of deionized water for dilution, start the stirring device, then add 20 g of the coating material, mature for 120 min, dry, and crush to obtain titanium dioxide for road sign paint.
[0080] Example 5
[0081] This embodiment discloses a method for preparing a modified dispersant, comprising the following steps:
[0082] Q1: 7.93 g of allyl alcohol polyoxyethylene ether and 0.033 mL of thioglycolic acid were mixed and added to a four-necked flask, and 50 mL of deionized water was added for dissolution. At the same time, 0.007 g of ammonium persulfate was dissolved in 10 mL of deionized water to obtain an ammonium persulfate solution, 1.3 mL of acrylic acid was dissolved in 20 mL of deionized water to obtain an acrylic acid solution, 15.81 mL of 3-(isobutylene acyloxy)propyl tris(trimethylsiloxane)silane was dissolved in 20 mL of methanol to obtain a silane solution, and the ammonium persulfate solution, acrylic acid solution and silane solution were connected to the four-necked flask by a constant flow pump, and the four-necked flask was heated;
[0083] Q2: When the temperature of the four-necked flask rises to 55°C, start to drop the ammonium persulfate solution, start to drop the acrylic acid solution 3 minutes later, and add the silane solution 8 minutes later. The dropping time is controlled to be 55 minutes. After the dropping is completed, keep the temperature for reaction for 5 hours;
[0084] Q3: After the heat preservation reaction is completed, the temperature is lowered to 28°C, the pH is adjusted to 7 with 30vt% sodium hydroxide, and the modified dispersant is obtained by rotary evaporation at 65°C.
[0085] This embodiment discloses a method for preparing a coating material, comprising the following steps:
[0086] S1: After mixing 1.34 mL of methyl methacrylate and 1.88 mL of butyl acrylate, 0.003 g of potassium persulfate was added, and the mixture was heated and stirred at 74°C for 0.5 h. After the reaction was completed, 2.11 g of 2-ethylhexyl acrylate was added, and the mixture was reacted at 74°C for 5 h to obtain an intermediate product;
[0087] S2: Add 1.43 mL of acrylic acid to 8.57 g of the intermediate product, heat to 82° C. for reaction for 0.5 h, and after the reaction is completed, obtain a coating material.
[0088] This embodiment discloses a method for preparing titanium dioxide for road marking paint, comprising the following steps:
[0089] Step (1): adding 4 g of the primary titanium dioxide product to 27 mL of a 40 wt% sodium hydroxide solution, heating and stirring at 65° C. for 8 h, washing and drying after the treatment to obtain modified titanium dioxide;
[0090] Step (2): 35 g of modified titanium dioxide was mixed with 45 mL of deionized water, and then crushed and wet-milled. Then, the wet-milled modified titanium dioxide was mixed with 4 g of a modified dispersant, and sand-milled using a vertical sand mill. The sand-milled slurry had a particle size of 0.25 μm and a particle size distribution of 1.33, thereby obtaining a sand-milled slurry.
[0091] Step (3): Add 27 g of the sand-ground slurry to a coating device with a stirring device, add 75 mL of deionized water for dilution, start the stirring device, then add 25 g of the coating material, mature for 120 min, dry, and crush to obtain titanium dioxide for road sign paint.
[0092] Comparative Example 1
[0093] Comparative Example 1 Compared with Example 1, in the process of preparing the modified dispersant in Comparative Example 1, no allyl alcohol polyoxyethylene ether was added, and other conditions remained unchanged.
[0094] Comparative Example 2
[0095] Comparative Example 2 Compared with Example 1, in the process of preparing the modified dispersant in Comparative Example 2, 3-(isomethacryloyloxy)propyltri(trimethylsiloxane)silane was not added, and other conditions remained unchanged.
[0096] Comparative Example 3
[0097] Comparative Example 3 Compared with Example 1, in the process of preparing the coating material in Comparative Example 3, methyl methacrylate is not added, and other conditions remain unchanged.
[0098] Comparative Example 4
[0099] Comparative Example 4 Compared with Example 1, in the process of preparing the coating material in Comparative Example 4, no acrylic acid is added, and other conditions remain unchanged.
[0100] Comparative Example 5
[0101] Comparative Example 5 Compared with Example 1, in the process of preparing titanium dioxide for road sign paint in Comparative Example 5, no modified dispersant is added, and other conditions remain unchanged.
[0102] Comparative Example 6
[0103] Comparative Example 6 Compared with Example 1, in the process of preparing titanium dioxide for road sign paint in Comparative Example 6, no coating material is added, and other conditions remain unchanged.
[0104] The samples prepared in Examples 1-5 and Comparative Examples 1-6 were subjected to performance tests. The samples were placed in a bulb-type light source yellowing resistance test box. The distance between the sample and the light source was kept at 25 cm under a 300W ultraviolet lamp. The temperature in the box was kept at 60°C. After irradiation for 3h and 6h, the chromaticity of the samples before and after treatment was measured using a JZ-300 universal colorimeter. The color difference was calculated based on the color difference = E 后 -E 前The discoloration grade was compared with that of GB / T 1766-2008. The sample was subjected to thermogravimetric analysis using a NETZSCH TG 209F1 differential thermal thermogravimetric analyzer. The temperature was gradually raised from room temperature to 300°C at a rate of 10K / min. The weight before and after treatment was measured. The mass reduction rate was calculated based on the mass reduction rate = [(m 前 -m 后 ) / m 前 ]×100%, the sample was coated on black glass with a coater with a groove depth of 200μm, and tested after being placed at room temperature for 7 days. The surface gloss was measured at 60℃ with CS-300 gloss agent. The test results are shown in Table 1:
[0105] Table 1
[0106] project Color change level Mass reduction rate / % Glossiness Example 1 0 0.013 98.64 Example 2 0 0.014 98.53 Example 3 0 0.014 98.32 Example 4 0 0.015 98.41 Example 5 0 0.015 98.27 Comparative Example 1 1 0.032 98.19 Comparative Example 2 2 0.035 98.15 Comparative Example 3 0 0.016 91.12 Comparative Example 4 0 0.016 90.20 Comparative Example 5 2 0.038 97.98 Comparative Example 6 0 0.017 88.93
[0107] It can be seen from the test results in Table 1 that by using the methods of Examples 1-5, the yellowing resistance, high temperature resistance and glossiness of titanium dioxide for road sign paint can be effectively improved. The higher the discoloration level, the worse the yellowing resistance; the higher the mass reduction rate, the worse the high temperature resistance. By comparing Comparative Example 1 with Examples 1-5, it can be found that the addition of allyl alcohol polyoxyethylene ether can effectively improve the yellowing resistance and high temperature resistance of titanium dioxide for road sign paint; by comparing Comparative Example 2 with Examples 1-5, it can be found that the addition of 3-(isobutyleneoxy)propyl tris(trimethylsiloxane) silane can effectively improve the yellowing resistance and high temperature resistance of titanium dioxide for road sign paint; by comparing Comparative Example 3 with Examples 1-5, it can be found that the addition of methyl methacrylate can effectively improve the gloss of titanium dioxide for road sign paint; by comparing Comparative Example 4 with Examples 1-5, it can be found that the addition of acrylic acid can effectively improve the gloss of titanium dioxide for road sign paint; by comparing Comparative Example 5 with Examples 1-5, it can be found that the addition of modified dispersant can effectively improve the yellowing resistance and high temperature resistance of titanium dioxide for road sign paint; by comparing Comparative Example 6 with Examples 1-5, it can be found that the addition of coating material can effectively improve the gloss of titanium dioxide for road sign paint.
[0108] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
[0109] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing titanium dioxide for road marking paint, characterized in that: The following steps are involved: Step (1): adding the primary titanium dioxide product to a sodium hydroxide solution, heating and stirring the solution, and after the treatment, washing and drying the solution to obtain modified titanium dioxide; Step (2): mixing the modified titanium dioxide with deionized water, crushing and wet-grinding the mixture, and then mixing the wet-grinded modified titanium dioxide with a modified dispersant, and sand-grinding the mixture to obtain a sand-grinded slurry; Step (3): Add the sand-ground slurry to a coating device with a stirring device, add deionized water for dilution, start the stirring device, then add the coating material, mature, dry, and crush to obtain titanium dioxide for road sign paint.
2. The method for preparing titanium dioxide for road marking paint according to claim 1, characterized in that: In the step (1), the ratio of the primary titanium dioxide to the sodium hydroxide solution is (3-8) g: (20-30) mL, the mass fraction of the sodium hydroxide solution is 40 wt %, the heating temperature is 60-70° C., and the stirring time is 6-8 h.
3. The method for preparing titanium dioxide for road marking paint according to claim 1, characterized in that: In the step (2), the amount ratio of modified titanium dioxide, deionized water and modified dispersant is (20-40) g: (30-50) mL: (2-5) g. A vertical sand mill is used in the sand milling process. The particle size of the sand milled slurry after sand milling is 0.2-0.3 μm, and the particle size distribution is 1.30-1.
38.
4. The method for preparing titanium dioxide for road marking paint according to claim 1, characterized in that: In the step (2), the preparation method of the modified dispersant comprises the following steps: Q1: Allyl alcohol polyoxyethylene ether and thioglycolic acid are mixed and added to a four-necked flask, and deionized water is added to dissolve them. At the same time, ammonium persulfate is dissolved in deionized water to obtain an ammonium persulfate solution, acrylic acid is dissolved in deionized water to obtain an acrylic acid solution, 3-(isobutyleneoxy)propyltri(trimethylsiloxane)silane is dissolved in methanol to obtain a silane solution, the ammonium persulfate solution, the acrylic acid solution and the silane solution are connected to the four-necked flask through a constant flow pump, and the four-necked flask is heated; Q2: When the temperature of the four-necked flask rises to the reaction temperature, start to drop the ammonium persulfate solution, then start to drop the acrylic acid solution, and finally drop the silane solution, control the dropping time, and after the dropping is completed, carry out the heat preservation reaction; Q3: After the heat preservation reaction is completed, the temperature is lowered, the pH is adjusted, and the modified dispersant is obtained by rotary evaporation.
5. The method for preparing titanium dioxide for road marking paint according to claim 4, characterized in that: In Q1, the molar ratio of allyl alcohol polyoxyethylene ether, acrylic acid and 3-(isobutyleneoxy)propyl tris(trimethylsiloxane)silane is (3-6):(1-2):(0.5-3); in Q2, the reaction temperature is 50-60°C, the acrylic acid solution is added dropwise after 3-5 minutes, and the silane solution is added dropwise after 6-10 minutes, and the dropping time is controlled to be 50-60 minutes, and the acrylic acid solution is added first, followed by the silane solution, and the ammonium persulfate solution is added last, and the insulation reaction time is 3-5 hours; in Q3, the temperature is lowered to 28-30°C, the pH is adjusted to 7-7.2 with 30vt% sodium hydroxide, and the rotary evaporation temperature is 60-70°C.
6. The method for preparing titanium dioxide for road marking paint according to claim 1, characterized in that: In the step (3), the usage ratio of the sand-grinding slurry, deionized water and coating material is (20-30) g: (60-80) mL: (18-27) g, and the aging time is 30-120 min.
7. The method for preparing titanium dioxide for road marking paint according to claim 1, characterized in that: The method for preparing the coating material comprises the following steps: S1: After mixing methyl methacrylate and butyl acrylate, potassium persulfate is added, and the mixture is heated and stirred for reaction. After the reaction is completed, 2-ethylhexyl acrylate is added and reacted to obtain an intermediate product; S2: Add acrylic acid to the intermediate product and heat to react. After the reaction is completed, a coating material is obtained.
8. The method for preparing titanium dioxide for road marking paint according to claim 7, characterized in that: In the S1, the molar ratio of methyl methacrylate, butyl acrylate and 2-ethylhexyl acrylate is (0.9-1.2):(1-1.2):(0.9-1.1), the heating temperature is 70-74°C, the reaction time is 0.5-1h, and the reaction temperature after adding 2-ethylhexyl acrylate is 70-74°C, and the reaction time is 5-5.5h.
9. The method for preparing titanium dioxide for road marking paint according to claim 7, characterized in that: In S2, the molar ratio of the intermediate product to acrylic acid is (0.9-1.2):(0.8-1.2), the heating temperature is 80-82°C, and the reaction time is 0.5-1h.
Citation Information
Cited By
True wear-resistant ceramic tile and preparation method thereof
CN120058233A